Proceedings of the 15th ACM Asia Conference on Computer and Communications Security 2020
DOI: 10.1145/3320269.3384746
|View full text |Cite
|
Sign up to set email alerts
|

Take A Way: Exploring the Security Implications of AMD's Cache Way Predictors

Abstract: To optimize the energy consumption and performance of their CPUs, AMD introduced a way predictor for the L1-data (L1D) cache to predict in which cache way a certain address is located. Consequently, only this way is accessed, significantly reducing the power consumption of the processor. In this paper, we are the first to exploit the cache way predictor. We reverse-engineered AMD's L1D cache way predictor in microarchitectures from 2011 to 2019, resulting in two new attack techniques. With Collide+Probe, an at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…Göktas et al [31] introduced the concept of a speculative probing primitive that leverages Spectre to break classical and fine-grained address space layout randomization. Gras et al [34], Schwarz et al [86], and Lipp et al [63] also demonstrated that microarchitectural attacks in JavaScript can break memory randomization. Hence, memory randomization is only a small obstacle that can be deterministically circumvented using engineering.…”
Section: B Building Blocksmentioning
confidence: 99%

Dynamic Process Isolation

Schwarzl,
Borrello,
Kogler
et al. 2021
Preprint
Self Cite
“…Göktas et al [31] introduced the concept of a speculative probing primitive that leverages Spectre to break classical and fine-grained address space layout randomization. Gras et al [34], Schwarz et al [86], and Lipp et al [63] also demonstrated that microarchitectural attacks in JavaScript can break memory randomization. Hence, memory randomization is only a small obstacle that can be deterministically circumvented using engineering.…”
Section: B Building Blocksmentioning
confidence: 99%

Dynamic Process Isolation

Schwarzl,
Borrello,
Kogler
et al. 2021
Preprint
Self Cite
“…In simultaneous multi-threaded (SMT) processors, various hardware resources are shared between two logical threads, thus other timing channels may be potentially created. Actually, recent work presented microarchitectural attacks exploiting timing channels existing on an execution port [38], translation look-aside buffer [39], [40], memory order buffer [41], [42] and way predictors [43].…”
Section: ) Cache Timing Attacksmentioning
confidence: 99%
“…We mainly focus on the x86 ISA (e.g., Intel and AMD) due to its wide adoption in modern PCs and servers, although some techniques can also be extended to the ARM processors [87,128]. Some works may need the processor to have additional hardware features such as Intel SGX [28,51,85,92,126,138,139,176,180,198,207,222], Intel TSX [61,108] and AMD's cache-way predictor [129]. We will mention the requirements when discussing these works.…”
Section: Threat Modelmentioning
confidence: 99%
“…Aciicmez et al [6] designed a side-channel attack against the RSA implementation in OpenSSL by distinguishing the multiplications from square operations. Flush-Reload [15,90,91,199,225] Flush-Flush [89], Reload+Refresh [33] Collide-Probe, Load-Reload [129] LRU state leaking [221] Requires KSM [129] Row buffer contention [158] Rambleed [123] Table 1. Side-channel attack vectors in hardware.…”
Section: Instruction Levelmentioning
confidence: 99%
See 1 more Smart Citation